PENGARUH PELATIHAN KERJA, KEPEMIMPINAN, DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN (Studi di PT MIDI UTAMA INDONESIA, Tbk Area Jakarta) - Nevin Utama (Universitas Mercu Buana, 2015)
Abstract. The retail business in Indonesia is now growing significantly, and the competitionis getting more strict and more open. To grow successfully and survive in the middle of astrict competition, the company need to notice the quality and performance of the humanresources. The purpose of this research is to know what is the impact of Work Training,Leadership and Work Environment to the quality of the employment (at Crew Level) atbranches of PT Midi Utama Indonesia in Jakarta. Convenience sampling was use as samplingmethod at taken by population of employees crew-level in Jakarta which totaled 1,212employees. Based on a population that exist with using slovin formulas, the margin error 10%then obtained a sample of respondents as many as 92 .The analysis method used in this studyis multiple regression. Results are showing that Work Training, Leadership, and WorkEnvironment have a significant impact on the employee's performance. The conclusion is thatemployee's performance at crew level at the brances of PT Midi Utama Indonesia in Jakartaare influenced by the Work Training, Leadership and Work Environment. To increase theemployee's performance, firm could plan and implement the training program design. On theother hand, every leader at each branches of PT Midi Utama Indonesia must improve a goodrelationship between it's employee so it will create a condusive work athmosphere. Thecompany slso need to notice the condition of work environment so all employees would workmore comfortably.Keywords: Job Training, Leadership, Work Environment, Employee Performance